2003
DOI: 10.1002/cne.10572
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of microglia in the developing rat brain

Abstract: Entrance of mesodermal precursors into the developing CNS is the most well-accepted origin of microglia. However, the contribution of proliferation and death of recruited microglial precursors to the final microglial cell population remains to be elucidated. To investigate microglial proliferation and apoptosis during development, we combined proliferating cell nuclear antigen (PCNA) immunohistochemistry, in situ detection of nuclear DNA fragmentation (TUNEL), and caspase-3 immunohistochemistry with tomato lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 90 publications
7
114
1
2
Order By: Relevance
“…In contrast, a study of developing embryonic rat brain found that apoptotic microglia constituted only a very small fraction of the entire microglial cell population until postnatal day 18. The authors postulated that apoptosis does not play a major role in regulating microglial density during development (40). However, with injury, apoptosis may be the primary mechanism of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of developing embryonic rat brain found that apoptotic microglia constituted only a very small fraction of the entire microglial cell population until postnatal day 18. The authors postulated that apoptosis does not play a major role in regulating microglial density during development (40). However, with injury, apoptosis may be the primary mechanism of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently it is accepted that microglia are myeloid lineage-derived cells that invade the CNS in the late prenatal and early postnatal periods. [41][42][43] Therefore, microglia and peripheral macrophages share many immunological markers.…”
Section: Lrp1 and Microglial Activation 591mentioning
confidence: 99%
“…Microglia are the resident immune cells of the CNS, which begin to colonize at early embryonic developmental stages (MarinTeva et al, 1998;Dalmau et al, 2003;Billiards et al, 2006;Rigato et al, 2011). In the mouse embryo, the colonization of the spinal cord (SC) by microglia involves several processes, including microglia proliferation at the periphery of the parenchyma (Rigato et al, 2011).…”
Section: Introductionmentioning
confidence: 99%